MANAGEMENT STRATEGY FORNPUBLICATION OF LASALLE COLLEGE INDONESIA’S ACHIEVEMENTS THROUGH FACEBOOK SOCIAL MEDIA - Yosika, Yosika (Jurnal Visi Komunikasi, 2022)
The use of social media Facebook as an alternative to new media in online publication activities to be able to reach a wider and targeted audience. As a result, there are more followers on LaSalle College Indonesia social media than other similar educational institutions. This research was conducted to find out how the management strategy of publications conducted by Lasalle College Indonesia through Facebook social media using the stages of managing publications from Manager Creations Publications "Brand Awareness Facebook". This study uses a qualitative approach with descriptive research types. The research method used is a single case study by conducting in-depth interviews with informants and conducting observation activities. The results of this study indicate that Lasalle College Indonesia uses Facebook as a media for publication of achievements to communicate its strategy in its aim to attract audience interest and reach wider target audiences to be interested in Lasalle College Indonesia by using soft selling. In its implementation there are several steps that are considered by Lasalle College Indonesia, namely determining the identification of the intended target audience, determining the type of publication content, determining the budget and publication schedule, placing the right publication, and formatting the content and text published on Facebook